Service quality, shariah compliance and customer satisfaction of Islamic Banking Services in Malaysia - Ahmed, Selim; Islam, Rafikul; Mohiuddin, Mohammad (Turkish Islamic Economists, 2017)
The present study investigates the level of service quality and customer satisfaction of Islamic banks in Malaysia based on demographics such as gender, nationality, experience with the bank and income. This study surveyed 179 customers who have had first-hand experience with Islamic banking services in Malaysia.The research data was analysed based on reliability analysis, independent samples t-tests and one-way ANOVA using SPSS ver¬sion 23. The research findings indicate that Malaysian customers have a better perception of reliability, respon¬siveness, assurance, empathy, tangibles and satisfaction compared to international customers. The findings also suggest that the customers who have 6–10 years’ experience with Islamic banking services, have a better perception of reliability, assurance and Shariah compliance compared to other experience groups.